Kebijakan Kampus Merdeka Mendorong Mahasiswa Berdaya Saing Global? - Ahmad Jahroni; Eli Fitriyani; Muhamad Faisal Hafiz (AGUSPATI RESEARCH INSTITUTA, 2025)
The purpose of this study is to find out the independent campus policy through merdeka Belajar. This study report uses a descriptive qualitative method by observing notes because the data source is obtained by listening to the oral narration from the KEMENDIKBUD RI Youtube channel entitled